2017
DOI: 10.1590/0104-6632.20170342s20150347
|View full text |Cite
|
Sign up to set email alerts
|

Real time and in situ Near-Infrared Spectroscopy (Nirs) for Quantitative Monitoring of Biomass, Glucose, Ethanol and Glycerine concentrations in an alcoholic fermentation

Abstract: -This study investigates the application of NIR spectroscopy for real-time monitoring of process parameters in alcoholic fermentations. For this purpose, fermentation batches using Saccharomyces cerevisiae were carried out and monitored in situ by an immersed NIRS probe. Samples were collected throughout the fermentations, and concentrations of biomass, glucose, ethanol and glycerin were analyzed by reference methods and multivariate data analyses such as PCA and PLSR. PCA was used to investigate data variabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 29 publications
2
22
0
Order By: Relevance
“…Substrate consumption shows two critical points of interest. In a previous study [16], validated models for real time prediction were also applied obtaining satisfying results, despite less accurate predictions, probably for two situations. In this case biomass, glucose and xylose are involved ( Fig.…”
Section: Real-time Monitoringmentioning
confidence: 98%
See 2 more Smart Citations
“…Substrate consumption shows two critical points of interest. In a previous study [16], validated models for real time prediction were also applied obtaining satisfying results, despite less accurate predictions, probably for two situations. In this case biomass, glucose and xylose are involved ( Fig.…”
Section: Real-time Monitoringmentioning
confidence: 98%
“…Miguel A. de Quevedo 2779, Col. Formando Hogar, CP 91860, Veracruz, México Abbreviation: %e, error percentage; MSC, multiplicative scattering correction; NIR, near-infrared; NIRS, near-infrared spectroscopy; PLSR, partial least square regression; VIP, variable influence in the projection of several advantages [1]; however, a major drawback of this species is that it cannot metabolize xylose [2], the most common sugar in hemicellulose and which represents a sizable fraction of lignocellulosic materials. Hence, near infrared spectroscopy (NIRS) can be applied as a real-time fermentation monitoring methodology using multiconstituent, rapid and nondestructive analyses, without involving sample pretreatment that leads to effective bioprocess control, a tool for increased yield, productivity, and reproducibility [14][15][16]. Nevertheless, the use of yeasts such as Pichia stipitis, naturally capable of metabolizing hexoses and pentoses, is a feasible solution for ethanol production from these renewable resources.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The goals of GAC is resource‐ and energy‐saving for analytical methods, too. Analyses should hence be operated in automation and at the same time be able to furnish as many parameters as possible requiring only a very little amount of sample or sample volume (Nascimento, Macedo, Santos, & Oliveira, ; Schalk et al, ; Villar et al, ). The use of spectroscopic methods enables the monitoring of all relevant process media in real time.…”
Section: Introductionmentioning
confidence: 99%
“…NIR spectroscopy is widely used in the fermentation, food, agricultural, petrochemical and pharmacological industries due to its rapid, noninvasive and economic advantages (H. Jiang et al, ; Tong, Du, Zheng, Wu, & Wang, ). In their study, do Nascimento, de Macedo, dos Santos, and de Oliveira () reported that NIRS can be utilized for actual‐time detecting of process factors in alcoholic fermentation. Andueza, Agabriel, Constant, Lucas, and Martin () used NIRS to achieve the ordering of cheese samples from various regimes.…”
Section: Introductionmentioning
confidence: 99%